Siperiaan - Punatähdet; Punander, Into; Punander, Kalervo; Punander, Karlos; Punander, Sauvo; Punander, Taisto Hiski; Punander, Uljas; Punander, Varma Kosto; Punanen, Aatos ([Punatähdet], 2009)
12 kappaletta.